Profiling of adoption and practice of conservation agriculture (CA) and CA-based mechanization in Ukama Ustawi project sites - Mkomwa, S.; Mutai, W.; Waswa, Boaz Shaban (Bioversity International and the International Center for Tropical Agriculture, 2023)
As part of the project implementation activities, ACT was task to profile CA and CA-based mechanization in the project sites to ascertain the status of adoption and practice and establish possible challenges that hinder massive and widespread adoption of the technologies. The study provided overview of CA practice status, actions by various stakeholders in the targeted Counties, recommend the best bet practices and scaling up of CA innovations for massive and greatest impact.